Studi Penurunan Glukosa Darah Diabet dengan Konsumsi Rumput Laut Eucheuma cottonii - Hardoko Hardoko (Universitas Gadjah Mada, 2007)
The purpose of this study was to observe the effect of Eucheuma cottonii consumption to the diabetic blood glucose level. Study on reducing blood glucose by consuming seaweed E. cottonii was conducted using male wistar rat (Ratus norvegicus). Rats were made to a hyperglycemic condition by aloxan injection before given ransom contains of 5, 10, 15, 20% (w/w) E. cottonii, standard ransom (negative control), and parental glibenklamid (positive control). The result showed that standard ransom was not able to reduce blood glucose from hyperglycemic to normal level, while ransoms with E. cottonii were able to do so. The higher E. cottonii seaweed level in the ransom had the higher capacity to decrease blood glucose level. The ransom with 20 and 15% E. cottonii were able to reduce blood glucose in 18 and 21 days, respectively.This treatment has the same ability as glibenklamid medicine which also reduced blood glucose to normal level in 18 days. Ransom with 5 and 10% E. cottonii were also able to reduce blood glucose level but the normal blood glucose level could not be achieved until 21st day.